Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/rs10010127
|View full text |Cite
|
Sign up to set email alerts
|

Role of El Niño Southern Oscillation (ENSO) Events on Temperature and Salinity Variability in the Agulhas Leakage Region

Abstract: This study explores the relationship between the Agulhas Current system and El

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our analysis of lagged correlations with the multivariate ENSO index reveals a 12-to 18-month lag of δ 18 O seawater and salinity at Ifaty and the AC region. These results agree with the 2-year lag found for the Agulhas leakage region, which is further downstream from our coral sites and implies a role for ENSO in interannual timescales of ocean connectivity (Potemra, 2001;Schouten et al, 2002;Wijffels and Meyers, 2004;de Ruijter et al, 2005;Palastanga et al, 2006;Putrahasan et al, 2016;Paris and Subrahmanyam, 2018). Salinity studies in the Agulhas leakage region have revealed a 20-to 26-month lag to ENSO forcing, whereby a fresh anomaly is replaced 2 years later by a saline anomaly following El Niño (and vice versa for La Niña) (Paris and Subrahmanyam, 2018;Trott et al, 2021).…”
Section: Large-scale Drivers Of Ac Core Region Sst and Salinitysupporting
confidence: 91%
See 1 more Smart Citation
“…Our analysis of lagged correlations with the multivariate ENSO index reveals a 12-to 18-month lag of δ 18 O seawater and salinity at Ifaty and the AC region. These results agree with the 2-year lag found for the Agulhas leakage region, which is further downstream from our coral sites and implies a role for ENSO in interannual timescales of ocean connectivity (Potemra, 2001;Schouten et al, 2002;Wijffels and Meyers, 2004;de Ruijter et al, 2005;Palastanga et al, 2006;Putrahasan et al, 2016;Paris and Subrahmanyam, 2018). Salinity studies in the Agulhas leakage region have revealed a 20-to 26-month lag to ENSO forcing, whereby a fresh anomaly is replaced 2 years later by a saline anomaly following El Niño (and vice versa for La Niña) (Paris and Subrahmanyam, 2018;Trott et al, 2021).…”
Section: Large-scale Drivers Of Ac Core Region Sst and Salinitysupporting
confidence: 91%
“…On interannual timescales, the AC and AL region is apparently sensitive to the El Niño-Southern Oscillation (ENSO), with a 24-month lag (Putrasahan et al, 2016;Elipot and Beal, 2018;Paris and Subrahmanyam, 2018;Trott et al, 2021). Anomalous wind stress curl in the southern Indian Ocean in response to ENSO excites the westward propagating oceanic Rossby waves (Feng and Myers, 2003;Palastanga et al, 2006;Grunseich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…SMAP is available from 2015 to present. Satellite-derived salinity has been used in several studies of the Indian Ocean but is underutilized in monsoon studies on the whole (Murty et al, 2004;Nyadjro et al, 2012;Nyadjro & Subrahmanyam, 2016;Paris & Subrahmanyam, 2018;Subrahmanyam et al, 2018).…”
Section: Data 211 Reanalysis Productsmentioning
confidence: 99%
“…Various studies of the linkage of the warm pool with large scale atmospheric circulation and oceanic processes have been launched [24][25][26][27]. The upper-layer volume fluctuations of the WPWP were found closely related to the oceanic circulation driven by the trade wind, and during El Niño events, the eastern sector volume increased yet the western sector decreased in much less magnitude [20].…”
Section: Introductionmentioning
confidence: 99%